Socratic Method and SOLO Taxonomy as Assessment Instruments During COVID-19 Pandemic - Aziz, N.A.A. (Springer Science and Business Media Deutschland GmbH, 2022)
The recent pandemic has brought a major shift in education sector worldwide. Online tools and platforms are continuously developed to aid teaching delivery and learning experience in the online environment. Online training and webinars are being held to assist the educators in this paradigm shift to familiarise educators on how to use the online tools. However, while trying to master the tools and systems, some educators have taken online assessment lightly by designing questions that could be searched online in a matter of seconds. Designing open book assessment with higher-order questions is still a great challenge by educators. In this chapter, the author discusses on Socratic method using SOLO Taxonomy that promotes learners to challenge their understanding from the fundamental knowledge gain during class. The designed assessment tool aids the course lecturer to evaluate the learners fairly on their knowledge and application of the topic, while providing questions using Socratic method of simple verbs and understandable question and provoke the thinking of the learners. The experience and reflections of using the combination of both concepts are shared in this chapter. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.